Are there any associations between single and/or multiple social roles and self-rated physical health, psychiatric disorder and long-term sickness absence in women? (Italian Journal of Public Health, 2012)
Background: The relationship between single and/or multiple social roles that women hold (occupa-tional, partner, and parent) and health and sickness absence is an important public health issue. Fewstudies on the social roles held by women have been performed in the Swedish context of gender equality.The aim of this study was to analyse associations between occupational, partner and parent roles (andcombinations of these roles) and their relation to self-rated physical health, psychiatric disorders andlong-term sickness absence in a population based sample of women in Sweden.MeThodS: Women born in 1935, 1945, 1955, 1965, 1970 or 1975 (n=600) were interviewed at baseline andfive years later. cross-sectional data were analysed with multivariate logistic regression analysis adjustedfor age, socio-economic position, alcohol dependence and abuse.reSulTS: an occupational role was associated with lower odds for poor self-rated physical health, 0.28(0.10-0.82), and sickness absence, 0.25 (0.10-0.86). a partner role was associated with lower odds for psy-chiatric disorder, 0.58 (0.35-0.98) while a parental role (children < 14 years) was associated with higherodds for sickness absence, 4.17 (1.86-9.38). The combination of holding an occupational and partnerrole was associated with lower odds for health outcomes compared with having three roles. conclusion:holding an occupational and partner role was related to lower odds for poor self-rated physical health,psychiatric disorder and long-term sickness absence, while having a parental role was adversely relatedto sickness absence. results are important in the light of discussions on reconciliation of work and family,and are of interest in countries with high or increasing female labour force participation.
Keywords: Multiple roles; Women; Self-rated health; Psychiatric disorder; Sickness absence